Effect of Skim Milk Powder and Whey Protein Concentrate Addition on the Manufacture of Probiotic Mozzarella Cheese - Khalid A. Alsaleem; Mahmoud E. A. Hamouda; Raed Reshaid Alayouni; Mohamed Salem Elfaruk; Ahmed R. A. Hammam (Fermentation, 2023)
This work aimed to study the effect of adding skim milk powder (SMP) and whey protein concentrate (WPC) to probiotic mozzarella cheese. Pasteurized cow milk was heated to 55 °C and divided into five parts: PMC1 (control), PMC2 (1% SMP), PMC3 (1.5% SMP), PMC4 (1% WPC), and PMC5 (1.5% WPC). After mixing powders in the respective concentrations in the treatments, the milk was cooled to 35 °C, and Bifidobacterium bifidum culture (5%) was added. Proximate analysis, calcium, soluble nitrogen (SN), total Bifidobacterium bifidum count, cheese yield, hardness, and meltability tests were carried out at 0, 14, and 28 days of storage. The mozzarella cheese samples with WPC added had higher acidity, total solids, and protein content than the mozzarella cheese samples with SMP added and the control samples during storage. The addition of WPC led to a significant increase (p < 0.05) in the count of Bifidobacterium bifidum during storage at 5 °C. The cheeses with WPC added had increased meltability, higher hardness, and higher browning on pizza compared to those of the mozzarella cheese with SMP added. A sensory evaluation showed that the addition of WPC increased sensory scores, compared to the addition of SMP. As storage time progressed, there was a significant (p < 0.05) increase in the Bifidobacterium bifidum, meltability, and sensory scores of PMC in all treatments.